The Effect Of Liquidity, Activity And Leverage Ratios On Profitability With Company Size As A Moderating Variable - Muh. Sahrul Ramadhani; Anwar; Rezky Amalia Hamka (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
The technology sector is a key driver of economic growth in today's digital era. However, during the 2021-2023 period, this sector experienced a decline in profitability, as reflected in the companies' financial reports. This issue is the background for this research, which aims to examine the influence of liquidity, activity, and leverage on profitability, as well as the potential mediating effect of firm size in technology sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The sample selection was carried out by purposive sampling to select company samples that met the criteria for this quantitative research, which uses the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The research findings indicate that while activity and leverage each have a positive but significant impact on profitability, liquidity has a negative but negligible impact. It also shows that firm size does not mediate the impact of activity, liquidity, and leverage on profitability; these findings support the Trade-off Theory regarding the importance of balance in the use of debt, but also indicate limitations in the application of Signaling Theory in the technology sector. This study concludes that high current assets reflect inefficient use of funds. Activity has a positive but insignificant influence, indicating that increased activity has not been accompanied by efficiency in asset management. Leverage also has a positive but insignificant influence, signaling that the use of debt has not been managed optimally. Furthermore, the relationship between liquidity, activity, and leverage on profitability cannot be mediated by organizational size.